Effectiveness of Cyanoacrylate in the Treatment of Dentin Hypersensitivity: A Systematic Review - Adriana da Silva Torres; Olga Beatriz Lopes Martins; Rejane Pereira Otoni; Kaio Henrique Soares; Marcelo Guimarães Torres; Parsa Firoozi; Olga Dumont Flecha (Hindawi Limited, 2023)
Objective. To compare the effectiveness of cyanoacrylate to other treatments or placebo in the management of dentin hypersensitivity (DH). Materials and Methods. The present review was organized based on the preferred reporting items for systematic reviews and meta-analysis (PRISMA) guidelines. The search aimed to answer the following question: is cyanoacrylate effective in the treatment of DH when compared to other treatments or placebo? The following databases were used: PubMed/MEDLINE, Scopus, BVS, Web of Science, Cochrane, Clinicaltrials.gov, Portal Periódicos Capes, Google Scholar, and manual search. The evaluation process started with the information collected from the selected articles according to the Consolidated Standards of Reporting Trials (CONSORT). Results. Two randomized and five nonrandomized clinical trials were analyzed in the qualitative synthesis. The studies presented different cyanoacrylate formulations, different scales for evaluating pain, and different methods for provoking a painful stimulus. Cyanoacrylate-based products reduce DH in shorter follow-up periods and this reduction persisted throughout the study. The results varied according to the methods used to stimulate the pain. Only two articles showed a low risk of bias and a high level of scientific evidence. Conclusion. Although there is a limited number of studies in the scientific literature with appropriate methodological quality, the available evidence proves the effectiveness of cyanoacrylate in the treatment of DH. Clinical Relevance. Cyanoacrylate is easy to access, effective, easily applicable, and a low-cost product with satisfactory results.